A New Approach of Localized Human Blood Reheating Using High Frequency Converter - Pradip Kumar Sadhu; Palash Pal; Animesh Halder; Ankur Ganguly; Nitai Pal; Prabir Bhowmik (Indonesian Journal of Electrical Engineering and Computer Science, 2015)
The paper presents the human blood reheating technique for medical purposes with high frequency induction heating system. The temperature is analyzed to determine the heat distribution in different positions of human blood within the non metallic tank. In the proposed induction heating system, the inductive applicator is a primary working coil of the modified half bridge high frequency inverter and the RBCs within the blood will be working as secondary element. The simulation shows that the heating area can be effectively controlled by using the cylindrical shield with adjustable space. However, the efficiency of heat can be increased by varying the radius size of cylinder thereby more flux appears and more eddy emf is induced. Hence the resulting eddy current increases the refrigerated blood of range 1ºC- 6ºC to 37ºC. DOI: http://dx.doi.org/10.11591/telkomnika.v14i1.7262